PP-008 Quality risk management: Microbiologic process validation for semisolid formulations using the failure mode effect analysis. (14th February 2016) - Engleder, E; Weigl, A; Pointinger, A
Abstract : Background: As a hospital pharmacy with a preparation unit, we offer a wide variety of products for individual patients as well as for stock. Since we hold a manufacturing license, we are obligated to comply with GMP rules (there are no hospital GMP guidelines in Austria), which is difficult for some aspects of hospital pharmacy preparations. In order to ensure quality for the safety of our patients, we therefore decide to do a combined process validation for defined product groups compared with single product validation and/or analysis. For many aspects of production (eg, shelf-life), we rely on the pharmaceutical literature or fulfil practical needs, very well aware that proof of the latter should be given. Purpose: To ensure microbial quality according to the European Pharmacopoeia (EuPh 8.0/5.1.4) for all our semisolid products and to verify defined shelf-lives from a microbiological point of view. Material and methods: Possible risks for microbiological contamination in our semisolids were identified by peer discussion. We used the failure mode effect analysis (FMEA) to quantify risks. This was done by incorporating frequency of occurrence, detectability and severity into a risk number. Based on this analysis, products with the highest risks were chosen for analysis. Their microbiological contamination was determined using the method and limits of the EuPh. Samples were either freshly prepared by different members of the production team or taken from stock or waste, ensuring to include samples at the end or over their shelf-lives. It was intended to extrapolate results to products with lower risks. Results: We identified 14 risk points of which absence or underdosing of preservatives, increasing content of water and batch volume had the highest risk. All of our 66 semisolids were included in the study of which 9 were considered the highest risk. Of these 9 products, 279 samples were analysed internally and 4 samples were sent for external examination. All results showed no microbiological contamination. Conclusion: We were able to show the microbiological quality of our products and validated our defined shelf-lives. We think that our approach of validation for a whole product group can help hospital pharmacies to prove quality in an acceptable practical way. No conflict of interest.